Malignant Bile Duct Obstruction: Role of a Multidisciplinary Team - Covey, Anne M.; Schattner, Mark (Digestive Disease Interventions, 2025)
Malignant bile duct obstruction (MBDO) can occur in patients with both primary liver cancers and metastatic disease and can be a cause of significant morbidity. Laboratory abnormalities or symptoms often prompt decompression to lower bilirubin for chemotherapy, treat cholangitis, and divert bile to treat a leak or alleviate pruritus. Intervention may also be undertaken to perform biopsy or provide access to intraductal therapies such as brachytherapy, photodynamic therapy, or radiofrequency ablation. There are multiple ways to achieve biliary decompression including percutaneous procedures performed by interventional radiologists, endoscopic procedures performed by advanced endoscopists, and biliary bypass performed by hepatobiliary surgeons. Which approach is undertaken depends on several factors including the performance status, life expectancy, level of obstruction, anatomy, and patient preference. Every intervention has inherent risks as well as potential benefits, and a review of these complex patients by a multidisciplinary team ensures all options are considered. Finally, some cases require the technique and expertise of more than one specialty to achieve the desired outcome. This article highlights the importance of a multidisciplinary team in dealing with MBDOs.
Keywords: biliary obstruction; malignant; multidisciplinary